О социальной структуре индоевропейской и кавказской общностей в раннем бронзовом веке - Берзин, Э.О. (1988)
Berzin, E.O., On the Social Structure of the Indo-European and the Caucasian Communities in the Early Bronze Age; English summary p.211-212